2001
DOI: 10.1093/humrep/16.10.2041
|View full text |Cite
|
Sign up to set email alerts
|

Experimental inoculation of male mice with murine cytomegalovirus and effect on offspring

Abstract: MCMV harboured in the male genital organs was not transmitted to their offspring, even when mating occurred during the acute phase of CMV disease. Although the infection may have had an impact on spermatogenesis, fertility was not affected. These results do not support the hypothesis of conceptus MCMV infection by the fertilizing spermatozoon in natural conception.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0
5

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 31 publications
1
10
0
5
Order By: Relevance
“…Thus, germ cells do not appear to be permissive to MCMV, whatever the immune status of the mice: immunocompetent or immunocompromised [CY-treated (this study), Nu/Nu mice (data not shown)]. These results are consistent with those of our previous study, which suggests that it was unlikely that the spermatozoon itself was directly infected with MCMV [15]. It is more likely that, if contamination of oocytes occurs, it is vectored by MCMV DNA found in the sperm which penetrates the oocyte during fertilization.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…Thus, germ cells do not appear to be permissive to MCMV, whatever the immune status of the mice: immunocompetent or immunocompromised [CY-treated (this study), Nu/Nu mice (data not shown)]. These results are consistent with those of our previous study, which suggests that it was unlikely that the spermatozoon itself was directly infected with MCMV [15]. It is more likely that, if contamination of oocytes occurs, it is vectored by MCMV DNA found in the sperm which penetrates the oocyte during fertilization.…”
supporting
confidence: 91%
“…An infection of Leydig cells leads to a transient degeneration of spermatogenesis in immunocompetent mice without affecting their offspring, which are like those of uninfected males [15].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…En trabajos realizados con un virus de otra especie, el CMVM (Citomegalovirus Murino), se encontró que al inyectarlo en los testículos de ratones se pudo aislar por diferentes té cnicas moleculares el DNA viral, tanto en las cé lulas espermá ticas inmaduras como en los espermatozoides maduros, causando adicionalmente infiltrados inflamatorios en el tracto reproductivo, infecció n de las cé lulas intersticiales y degeneració n de los tú bulos seminíferos, siendo las cé lulas de Leydig el blanco predilecto para la invasió n del virus 25 . Lo que má s se acepta hasta el momento, es que el virus se adhiere primero al heparan sulfato, pero su entrada final a la cé lula está mediada por alguno de esos receptores desconocidos.…”
Section: Citomegalovirus Humanounclassified